Economic Growth in Rural Areas, Resource Agglomeration, and Stock Market Performance: Evidence from China - Guojing Geng (International Journal of Financial Studies)
This study aims to explore the potential association between the performance of the stock market and the growth of the rural economy in China. It examines the impact of regional market volatility on rural macroeconomic indicators, which functions through the equity price fluctuations of locally listed firms. The analysis utilizes financial performance data from publicly traded companies across 283 prefecture-level cities within 31 provinces in China, spanning from 1996 to 2021. This research documents a resource agglomeration effect, which is induced by the inflow of various resources by listed companies into their respective regional areas, and which emerges as the key driver for the development of the rural economy in those regions. Additionally, this study uncovers the advantages of the risk diversification effect that arises from the aggregation of resources. These findings have three significant implications. First, both effects are identified as concurrent mechanisms without any evidence of a crowding-out effect. Secondly, multiple avenues are presented through which financial capital can affect the rural economic development of a region. Lastly, this study suggests specific strategies for assessing the equity market’s role in ensuring the sustainable development of the Chinese rural economy.